The Influence of Promotion, Product Quality, Service Quality, Convenience, Security, and Trust on Customer Satisfaction of Dana E-Wallet Users (International Forum of Researchers and Lecturers, 2024)
The growing number of e-wallet users indicates a rise in customer satisfaction with the DANA e-wallet from 2021 to 2023. This research aims to determine and test the influence of promotion, product quality, service quality, convenience, security, and trust on customer satisfaction among E-Wallet DANA users. This research employs a quantitative methodology. This research employs a non-probability sampling technique, known as the accidental sampling method, for its sample collection. We collected research data by distributing questionnaires to 97 respondents, utilizing data analysis techniques such as multiple linear regression analysis with the assistance of SPSS. The research results show that promotion, product quality, service quality, convenience, security, and trust have a positive effect on customer satisfaction among DANA application users.